2013
DOI: 10.2466/10.06.pms.117x22z7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fundamental Motor Skills and Physical Activity in 4-Year-Old Preschool Children

Abstract: This study evaluated the relationships between objectively measured physical activity and fundamental motor skills in 4-year-old children. Physical activity was monitored in 20 girls and 17 boys over 5 consecutive days (3 days at preschool and 2 days at home) and their fundamental motor skills measured. Multiple linear regressions controlled for sex, age, and body mass index indicated that the total skill score was significantly associated with physical activity, explaining 13%, 16%, and 16% of the variance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 32 publications
5
87
3
6
Order By: Relevance
“…However, competence levels were only marginally lower than those reported in similar-aged counterparts from more representative SES samples ( Ulrich, 2000 ;Hardy, King, Farrell, et al ., 2010 ). Previous cross-sectional studies among preschoolers have found positive associations between FMS competence and objectively measured light, moderate-to-vigorous, and total daily physical activity ( Fisher, et al ., 2005 ;Williams, et al ., 2008 ;Cliff , et al ., 2009 ;Burgi, et al ., 2011 ;Iivonen, et al ., 2013 ;Foweather, et al ., 2014 ). This relationship is considered bi-directional, with participation in physical activity thought to drive gains in FMS competence through a "positive feedback loop" ( Barnett, Morgan, Van Beurden, Ball, & Lubans, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, competence levels were only marginally lower than those reported in similar-aged counterparts from more representative SES samples ( Ulrich, 2000 ;Hardy, King, Farrell, et al ., 2010 ). Previous cross-sectional studies among preschoolers have found positive associations between FMS competence and objectively measured light, moderate-to-vigorous, and total daily physical activity ( Fisher, et al ., 2005 ;Williams, et al ., 2008 ;Cliff , et al ., 2009 ;Burgi, et al ., 2011 ;Iivonen, et al ., 2013 ;Foweather, et al ., 2014 ). This relationship is considered bi-directional, with participation in physical activity thought to drive gains in FMS competence through a "positive feedback loop" ( Barnett, Morgan, Van Beurden, Ball, & Lubans, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most evidence indicates that a substantial proportion of preschool aged children do not meet the widely accepted World Health Organization (WHO) guidelines (WHO, 2010) of at least 60 min of moderate- to vigorous-intensity physical activity (MVPA) per day (Hnatiuk et al, 2014), but rather spend most of their waking hours engaged in sedentary behavior (Kelly et al, 2007, Reilly et al, 2004). Insufficient MVPA levels and high amounts of sedentary time are associated with high systolic blood pressure (Vale et al, 2015), poor motor skills (Iivonen et al, 2013) and low cardiorespiratory fitness (Burgi et al, 2011) in preschool children. Moreover, both lack of MVPA and high sedentary time are implicated in the etiology of childhood obesity (Troiano and Flegal, 1998, Reilly et al, 1999) and children tend to carry this excessive adiposity into adulthood (Jimenez-Pavon et al, 2010, Rey-Lopez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the better a child's motor skills, the more possibilities she or he has to be physically active, and vice versa, the better a child's motor skills, the more physically active she or he is . For instance, locomotor skills, measured by the sliding and galloping tests were positively associated with children's MVPA, and manipulative skills measured by throwing and catching combination test, were positively associated with both total PA and light to vigorous intensity PA (LMVPA) (Iivonen et al, 2013). It is noteworthy that PA patterns are only guidelines and that considerable variation in stage of development exists across children of the same age (Gallahue & Ozmun, 2006, p. 193).…”
mentioning
confidence: 99%